The cultivation of human granulosa cells - Brůcková, Lenka; Soukup, Tomás; Moos, Jirí; Moosová, Martina; Pavelková, Jana; Rezábek, Karel; Vísek, Benjamin; Mokrý, Jaroslav (Acta medica (Hradec Kralove), 2008)
The major functions of granulosa cells (GCs) include the production of steroids, as well as a myriad of growth factors to interact with the oocyte during its development within the ovarian follicle. Also FSH stimulates GCs to convert androgens (coming from the thecal cells) to estradiol by aromatase. However, after ovulation the GCs produce progesterone that may maintain a potential pregnancy. Experiments with human GCs are mainly focused on the purification of GCs from ovarian follicular fluid followed by FACS analysis or short-term cultivation. The aim of our study was to cultivate GCs for a long period, to characterize their morphology and phenotype. Moreover, we have cultivated GCs under gonadotropin stimulation in order to simulate different pathological mechanisms during folliculogenesis (e.g. ovarian hyperstimulation syndrome). GCs were harvested from women undergoing in vitro fertilization. Complex oocyte-cumulus oophorus was dissociated by hyaluronidase. The best condition for transport of GCs was optimized as short transport in follicular fluid at 37 degrees C. GCs expansion medium consisted of DMEM/F12, 2% FCS, ascorbic acid, dexamethasone, L-glutamine, gentamycine, penicillin, streptomycin and growth factors (EGF, bFGF). GCs transported in follicular fluid and cultivated in 2% FCS containing DMEM/F12 medium supplemented with follicular fluid presented increased adhesion, proliferation, viability and decreased doubling time. Cell viability was 92% and mean cell doubling time was 52 hrs. We have optimized transport and cultivation protocols for long-term cultivation of GCs.
Keywords: Granulosa Cells; kultivační média; Female; Adult; dospělí; folikulární buňky; Cell Culture Techniques; ženské pohlaví; Humans; lidé; Culture Media; buněčné kultury